Cooperative passenger flow control in an oversaturated metro network with operational risk thresholds - Shi, Jungang; Yang, Lixing; Yang, Jing; Zhou, Feng; Gao, Ziyou (Transportation research. Part C, Emerging technologies, 2019)
•A network-based passenger flow control method is proposed for the oversaturated metro network.•A bi-objective integer linear programming model is formulated.•The equivalent single objective linear integer programming model is deduced.•Numerical examples demonstrate the effectiveness of the proposed approaches. The oversaturated situation is now very common in the metro system of some megacities due to large commuting demands in peak hours, which leads to passenger accumulation on platforms and causes potential accident risks. To improve the transport efficiency and passenger accumulation safety at each station, this paper proposes a cooperative passenger flow control optimization in a specific metro network, in which each passenger can freely switch trains between different metro lines with a single ticket. Through considering the dynamic characteristics and transfer behaviors of passengers, an effective bi-objective integer linear programming model is formulated to characterize the passenger control process, in which the objectives are to minimize the total passenger waiting time and passenger accumulation risks at all the involved stations. To solve the proposed model conveniently, the above model is transformed into a single-objective model through reformulating the risk objective as a threshold-based constraint. Finally, two sets of numerical experiments, including a small-scale case and a real-world instance with operation data of the Beijing metro system, are implemented to demonstrate the performance and effectiveness of the proposed approaches.